ELEMEN NATURE IN THE SPACE PADA BANGUNAN WORK HUB DI CEMPAKA PUTIH, JAKARTA PUSAT - Amadea Gita Larasati Baginda; Uras Siahaan; Sally S. Napitupulu (UKI Press, 2026)
ABSTRACT Nowadays, people tend to work remotely, so they don't need large offices. Conventional offices tend to be too formal and stressful, making workers unable to work optimally. In addition, these offices are usually centralized only in city office areas, which makes them prone to traffic jams and difficult to reach for those who live far away. This is why the need for work hubs continues to increase. Work hubs are the right solution for individuals and small companies who want to be creative in a flexible, relaxed, strategic, and stress-free environment. Work hubs are more relaxed than conventional offices, but support interaction between workers like cafes, while minimizing distractions. Work hubs also eliminate the sense of isolation that people who work in home cafes feel. A comfortable and non-stressful work environment can support productivity and human interaction in it. One approach that supports this is nature in the space. This approach integrates nature into the building. Nature in the space can be realized by applying natural elements to buildings, that are related to human senses. This approach has been proven to reduce stress and fatigue in humans. In addition, the building mass will be analyzed in terms of linkage, site potential, climatology, and accessibility, to produce a design as a solution that answers all the problems that exist on the site. This work hub design, with a nature in the space approach, involves the use of rooftop gardens and irrigation. Therefore, a proper structural system that can withstand the load given by the plants, soil and water will be required. Keywords: Coworking Space; Nature in The Space; Work Hub